Hyponatremia and hypernatremia are associated with increased 30-day mortality in hip fracture patients. Issue 1 (January 2016) - Madsen, C.; Jantzen, C.; Lauritzen, J.; Abrahamsen, B.; Jorgensen, H.
Abstract Summary Using data from the Danish national registries on 7317 patients, this study shows that abnormal plasma sodium levels, in the form of hyponatremia and hypernatremia, are prevalent and associated with increased 30-day mortality in hip fracture patients. Introduction The aim of this study was to examine the prevalence of hyponatremia and hypernatremia in patients admitted with a fractured hip as well as the association with 30-day in mortality in these patients. Methods A total of 7317 hip fracture patients (aged 60 years or above) with admission plasma sodium measurements were included. Data on comorbidity, medication, and death was retrieved from Danish national registries. The association between plasma sodium and mortality was examined using Cox proportional hazard models. Results The prevalence of hyponatremia and hypernatremia on admission was 19.0 and 1.7 %, respectively. Thirty-day mortality was increased for patients with hyponatremia (12.2 %, p = 0.005) and hypernatremia (15.5 %, p = 0.03) compared to normonatremic patients (9.6 %). After adjustment for possible confounding factors, hyponatremia (1.38 [1.16–1.64], p = 0.0003) and hypernatremia (1.71 [1.08–2.70], p = 0.02) were still associated with increased risk of death by 30 days. Looking at the association between changes in plasma sodium during admission and mortality, there was no difference between patients with normalized and persistent hyponatremia (10.4 vs 11.3 %, p = 0.6) while a lower mortality was found for normalized hypernatremia compared to persistent hypernatremia (12.4 vs 33.3 %, p = 0.03). Conclusions This study shows that abnormal plasma sodium levels are prevalent in patients admitted with a fractured hip and that both hyponatremia and hypernatremia are associated with increased risk of death within 30 days of admission.